Pemimpin Yang Adil Dalam Al-Qur’ān (Studi Komparasi Ayat-Ayat Kepemimpinan Menurut Tafsīr Ibnu Kaṡīr dan Tafsīr Sayyid Quṭhb) - Fauzi, Muhammad; Harahap, Mardian Idris; Nasution, Muhammad Roihan (Jayapangus Press, 2024)
Leadership is a very urgent matter in the Islamic view. This can be seen in surah al-Mā’idah verse 59 which talks about the command to obey Allah, His Messenger and leaders. In the mechanism for selecting a leader, Islam does not provide implementation and technical instructions in the regulations on the procedures for appointing and dismissing a leader. A country that has diversity of religions, ethnicities, races, languages, cultures and natural riches certainly needs leaders who are not only physically strong, but also capable of solving problems that occur. This research aims to explore just leaders in the Al-Qur’ān and analyze the views of Ibn Kaṡīr and Sayyid Quṭhb regarding the Al-Qur’ān verses about just leaders. This research is descriptive-analytic in nature where the author compares Tafsīr Al-Qur'ān al-'Aẓīm and Fī Ẓilāl Al-Qur’ān about just leaders. This study found that just leadership in the Al-Qur'ān can be applied into seven parts including: Khalīfah, imāmah, ulu al-‘Amr, sulṭān, mulk, qawwāmah, wilāyah/auliyā. As for a just leader, according to Ibn Kaṡīr and Sayyid Quṭhb, a leader must be fair to everyone, whether they are known and still have a kinship relationship or not at all. Justice is the right of all humans, so it is their identity as a human that makes them entitled to justice.